2007
DOI: 10.1038/nmat1934
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing materials with microvascular networks

Abstract: Self-healing polymers composed of microencapsulated healing agents exhibit remarkable mechanical performance and regenerative ability, but are limited to autonomic repair of a single damage event in a given location. Self-healing is triggered by crack-induced rupture of the embedded capsules; thus, once a localized region is depleted of healing agent, further repair is precluded. Re-mendable polymers can achieve multiple healing cycles, but require external intervention in the form of heat treatment and applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
946
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,418 publications
(954 citation statements)
references
References 21 publications
1
946
3
4
Order By: Relevance
“…the healing of a small cut in skin and fractured bones. Mimicking biological systems, a number of synthetic materials have now been designed with the ability to spontaneously restore their mechanical properties and functions upon damage [1][2][3][4][5]. Over the last few years, self-healing has been observed in a wide range of nanostructured materials, such as ceramic nanocrystals, carbon nanotube and graphene [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the healing of a small cut in skin and fractured bones. Mimicking biological systems, a number of synthetic materials have now been designed with the ability to spontaneously restore their mechanical properties and functions upon damage [1][2][3][4][5]. Over the last few years, self-healing has been observed in a wide range of nanostructured materials, such as ceramic nanocrystals, carbon nanotube and graphene [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, self-healing has rarely been observed in GaAs NWs with lateral dimensions more than 12 nm. Moreover, there is a practical interest in developing materials that can achieve multiple healing cycles [5]. Our recent in situ observations have revealed that GaAs NWs possess the ability to heal themselves when subjected to repeated fractures [10].…”
Section: Introductionmentioning
confidence: 99%
“…In animals, this is possible by the continuous flow of an intelligent mixture of biochemicals in the vascular net work, which is related to the circulatory system. Some at tempts are made to mimic vascular network for self-heal ing [104,107], where a constant supply of healing agent could potentially be provided. There are several manufac turing issues involved here, and opens up many potential research avenues.…”
Section: Self-healing Compositesmentioning
confidence: 99%
“…Epoxy matrices containing integrated networks filled with active fluids have demonstrated the ability to indicate internal damage [1][2][3][4] as well as to autonomously heal from single [4][5][6] and repeated 5,7,8 damage events. In this respect, these systems bear a significant resemblance to natural vasculature, which functions to transport fluids throughout biological tissue for various functions including, but not limited to self-healing.…”
mentioning
confidence: 99%
“…In contrast, scaffold-based networks are formed by the fabrication of an arbitrarily shaped template from a fugitive material that is then surrounded with an epoxy matrix, and removed, leaving a series of interconnected hollow channels. 7,8,[23][24][25][26] Our research group has studied networks made using direct-write assembly, in which a hydrocarbon microcrystalline wax is extruded to form the scaffold using robotically controlled deposition. 27 With appropriate methods of scaffold fabrication, the advantage of this second method is greater control over network design as channels can have non-linear shapes and linkages, but due to the absence of load-bearing glass fibers these materials experience a reduction in bulk mechanical properties.…”
mentioning
confidence: 99%